2008
DOI: 10.1200/jco.2007.11.5964
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of O6-Methylguanine Methyltransferase (MGMT) Promoter Methylation With Clinical Outcomes in Glioblastoma and Clinical Strategies to Modulate MGMT Activity

Abstract: Correlation of O6-methylguanine methyltransferase (MGMT) promoter methylation with clinical outcomes in glioblastoma and clinical strategies to modulate MGMT activity AbstractResistance to alkylating agents via direct DNA repair by O(6)-methylguanine methyltransferase (MGMT) remains a significant barrier to the successful treatment of patients with malignant glioma. The relative expression of MGMT in the tumor may determine response to alkylating agents, and epigenetic silencing of the MGMT gene by promoter me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
523
2
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 725 publications
(569 citation statements)
references
References 72 publications
(76 reference statements)
16
523
2
15
Order By: Relevance
“…42 Once the tumor has developed, decreased DNA repair gene expression can however be beneficial to the patients by increasing the sensitivity of the tumor cells to DNA-damaging therapies, as shown for MGMT hypermethylation in glioblastoma. 43 In our study, patients with high NEIL1 methylation showed a significantly higher recurrence-free survival but this was not apparent after stratification by tumor localization. The statistical power of our study cohort might however be too small for a stratified analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…42 Once the tumor has developed, decreased DNA repair gene expression can however be beneficial to the patients by increasing the sensitivity of the tumor cells to DNA-damaging therapies, as shown for MGMT hypermethylation in glioblastoma. 43 In our study, patients with high NEIL1 methylation showed a significantly higher recurrence-free survival but this was not apparent after stratification by tumor localization. The statistical power of our study cohort might however be too small for a stratified analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…18,19 A biomarker test for MGMT status needs to be standardized, suitable for high-throughput analyses and reproducible in independent laboratories, and must have a clinically relevant cut-off point. The test should allow prospective patient selection and individualized therapy, thereby pursuing the strategy of personalized medicine for patients with brain tumors.…”
Section: Assessing Mgmt Status In Tumor Tissuementioning
confidence: 99%
“…The sensitivity of gliomas to TMZ is tightly correlated to the expression of the DNA repair enzyme MGMT (40). Therefore, we compared MGMT-positive U87 cells (41, 42) with MGMT-negative U343 cells (43) and analyzed the extent of cell death after treatment with 5, 10, and 15 μmol/L of (±)-gossypol and (−)-gossypol either with or without 100 μmol/L TMZ for 96 hours.…”
Section: Temozolomide Potentiates Autophagy and Cell Death Induced Bymentioning
confidence: 99%